GRP78 Impairs Production of Lipopolysaccharide-Induced Cytokines by Interaction with CD14 - Qin, Kai; Ma, Simin; Li, Heli; Wu, Min; Sun, Yuanli; Fu, Mingpeng; Guo, Zilong; Zhu, Huifen; Gong, Feili; Lei, Ping; Shen, Guanxin (Frontiers in Immunology, 2017)
The 78-kDa glucose-regulated protein (GRP78) is a stress-inducible chaperone that resides primarily in the endoplasmic reticulum. GRP78 has been described to be released at times of cellular stress and as having extracellular properties that are anti-inflammatory or favor the resolution of inflammation. In the current study, we confirmed that GRP78 impaired the production of lipopolysaccharide-induced pro-inflammatory cytokines in GRP78-treated bone-marrow-derived dendritic cells (DCs). To explore the underlying mechanism, first of all, GRP78 was checked to be bound to the plasma membrane. Interestingly, such binding promoted endocytosis of toll-like receptor (TLR) 4 and reduction in TLR4 on the plasma surface had a key role in desensitization of GRP78-treated DCs to lipopolysaccharide. Given that cluster of differentiation (CD)14 is a crucial regulator of TLR4 endocytosis, interaction of GRP78 with CD14 was investigated next. Data showed that GRP78 co-localized with CD14 on the plasma membrane and glutathione-S-transferase-GRP78 precipitated CD14. In CD14 knockout mice, down-regulation of tumor necrosis factor-α and reduction in TLR4 on the plasma surface were abrogated in GRP78-treated DCs. Overall, these data suggested that GRP78 mediates endocytosis of TLR4 by targeting CD14 to favor the resolution of inflammation.